2016
DOI: 10.1002/jbm.b.33777
|View full text |Cite
|
Sign up to set email alerts
|

Biokinetics and tissue response to ultrananocrystalline diamond nanoparticles employed as coating for biomedical devices

Abstract: Although Ultrananocrystalline diamond (UNCD) has been proposed as a coating material for titanium biomedical implants, the biological effects and toxicity of UNCD particles that could eventually detach have not been studied to date. The biokinetics and biological effects of UNCD compared to titanium dioxide (TiO ) nanoparticles was evaluated in vivo using Wistar rats (n = 30) i.p. injected with TiO , UNCD or saline solution. After 6 months, blood, lung, liver, and kidney samples were histologically analyzed. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…26,27 A study using 16S RNA sequencing to analyze adjacent peri-implant and periodontal microbiomes in states of health and disease found that 85% of individuals shared less than 8% of abundant species between teeth and implants. 28 Furthermore, peri-implant communities demonstrated less diversity than periodontal microbial communities. 28 The important observation of a distinct microbial signature in peri-implantitis compared with periodontitis [28][29][30] necessitates research on the capability of the host to mount or potentially resolve an inflammatory response against peri-implant bacteria.…”
Section: The Peri -Impl Ant MI Crob I Ota Re S Is Ts Periodontal Anmentioning
confidence: 99%
See 3 more Smart Citations
“…26,27 A study using 16S RNA sequencing to analyze adjacent peri-implant and periodontal microbiomes in states of health and disease found that 85% of individuals shared less than 8% of abundant species between teeth and implants. 28 Furthermore, peri-implant communities demonstrated less diversity than periodontal microbial communities. 28 The important observation of a distinct microbial signature in peri-implantitis compared with periodontitis [28][29][30] necessitates research on the capability of the host to mount or potentially resolve an inflammatory response against peri-implant bacteria.…”
Section: The Peri -Impl Ant MI Crob I Ota Re S Is Ts Periodontal Anmentioning
confidence: 99%
“…28 Furthermore, peri-implant communities demonstrated less diversity than periodontal microbial communities. 28 The important observation of a distinct microbial signature in peri-implantitis compared with periodontitis [28][29][30] necessitates research on the capability of the host to mount or potentially resolve an inflammatory response against peri-implant bacteria. While it is likely that the oral taxa that colonize implant biomaterial surfaces originate from dental biofilms, crevicular and extra-crevicular reservoirs.…”
Section: The Peri -Impl Ant MI Crob I Ota Re S Is Ts Periodontal Anmentioning
confidence: 99%
See 2 more Smart Citations
“…TiO 2 particles induced necrosis and cell membrane damage accompanied by generation of reactive oxygen species both in lung and liver tissue. Conversely, none of these effects were observed in the case of UNCD nanoparticles [ 79 ].…”
Section: Diamond Biocompatibilitymentioning
confidence: 99%